Pengaruh Pembelajaran Etnomatematika Sunda Permainan Engklek Terhadap Kemampuan Pemahaman dan Disposisi Matematis Siswa SD - Maqin, Jeany Arsy; Supriadi, Supriadi (Didaktika, 2022)
In this study, researchers carried out mathematics learning activities with Sundanese ethnomathematics through Engklek games. This study aims to determine the ability of students' understanding after being given treatment through Sundanese ethnomathematics learning compared to expository learning, and the results of student dispositions after learning with Engklek games. The research approach using the experimental method by purposive sampling found two iv classes, namely the IVA class given the Sundanese ethnomathematics learning treatment as an experimental class and the control class with expository learning in class IVB with the number of students per class of 25 people. The instruments used are question tests, LKS, observation sheets, disposition questionnaires for experimental classes, daily journals, and interviews. After being given a different treatment, it showed that the mathematical comprehension ability of the experimental class students obtained good results from the control class with an average posttest score of class IVA 76.6 and class IVB 66.2 by looking at the significance results of 0.003, which was less than 0.05 on the t-test. The mathematical disposition and response of the experimental class showed positive results, judging from the average score of 77% belonging to the good category. So it can be concluded that the learning of Sundanese ethnomathematics greatly affects students' ability to understand and disposition mathematically